Common cold - Eccles, Ronald (Frontiers in Allergy, 2023)
The common cold is a unique human disease, as it is arguably the most common disease and because of the large number of respiratory viruses causing colds it is one of the most complex of human diseases. This review discusses the respiratory viruses and notes that all these viruses may cause the illness complex recognised as the common cold. The common cold is discussed as part of the "iceberg concept" of disease which ranges from asymptomatic infection to severe illness and death. The factors influencing the incidence of colds are discussed: crowding and sociability, stress, smoking and alcohol, immune status, sex, age, sleep, season, chilling, nutrition and exercise. The mechanism of symptoms related to the innate immune response is explained and symptomatic treatments are tabulated. Morbidity associated with common cold is discussed and possible vaccines.